Collaboration Between Humans and Robots in Organizations: A Macroergonomic, Emotional, and Spiritual Approach - Firescu, Violeta; Gaşpar, Mirabela-Luciana; Crucianu, Ioan; Rotariu, Eliade (Frontiers in Psychology, 2022)
The new managerial challenges are related to finding solutions for complex problems, inside some more and more complex management systems, in a continuously changing organizational context. Competitivity and progress imply a continuous positive change and the need to accept, respond, and adapt to the organization’s internal and external environments changes. This brief research report aims to point out the organizational ergonomics’ contribution to employees’ wellbeing through a systemic, emotional, and spiritual approach to man’s interaction with technology, systems, and organizational environment. The research methods used were the multidisciplinary bibliographic study and the interview. Three semi-structured interviews were taken to explore today’s challenges and new 4.0 technologies’ impact, especially robots, on the company and on employees’ wellbeing and spiritual fulfillment. The novelty comes from the analysis of new technologies’ impact on the human factor from the spiritual point of view. Our main results have to do with the shaping of a model for human capital’s valorization and with suggesting a list for monitoring human capital valorization in the company. This article’s main conclusion shows that the organizations’ management must be prepared to manage future challenges by improving the employee’s abilities, adaptability to change, and collaboration with robots.